PEMBERDAYAAN MASYARAKAT SEBAGAI UPAYA UNTUK MEMBANGUN MASYARAKAT YANG SADAR DAN TANGGAP DALAM MENGHADAPI PANDEMI COVID-19 - Listyani R, Lisa; Qisty B, Aulia; Permatasari, Iasae; Putri N, Andini (Lembaga Pengkajian dan Pengembangan Masyarakat, Yayasan Cahaya Mulia Mandiri, 2021)
The purpose of the Service for the Community (PMM) is a form of student service through the provision of empowerment assistance, training, counseling, mentoring to raise awareness about potential, and help to improve the quality of life. During the current pandemic, this PMM activity also aims to educate and awaken the mindset of the village community about the dangers of the COVID-19 virus. The results of this service are the achievement of community welfare, being able to continue to develop the potential that exists in themselves, continue to create a healthy living culture and help rural communities in breaking the chain of the Covid-19 virus.